A pragmatic assessment of contextual fit and feasibility for e-learning implementation among public health workers in 16 West African countries: a mixed-methods study - Kehinde O. Ogunyemi; Virgil K. Lokossou; Lionel S. Sogbossi; Chima Ohuabunwo; Simon Antara; Senait Kebede; Carol Haley; Tolbert Nyenswah; Melchior A. Aïssi; Scott McNabb (International Society of Global Health, 2024)
# Background E-learning plays a key role in bridging competency gaps among the public health workforce to prevent, detect, and respond to public health emergencies. However, its implementation remains a challenge in resource-limited settings. In this study, we assessed the contextual fit and feasibility of a multi-communication online training (MOT) for its effective implementation. # Methods A mixed-methods study was conducted among public health workers in 16 West African countries between Aug 10, 2023, and Oct 10, 2023. Data were collected through an online survey and in-depth interviews. Through a One Health forum and subregionally coordinated efforts, participants were sampled for the survey and interviews using virtual snowball and voluntary response techniques respectively. Contextual fit was measured with MOT preference and acceptability, while feasibility was measured with MOT willingness to use and workplace ICT availability using a novel tool. Statistical weighting was applied, and interviews were thematically analysed. Quantitative data were analysed using SAS version 9.4 with inverse probability weights and post-stratification weights at the country level. Descriptive statistics were summarized as unweighted and weighted frequencies and weighted proportions. Rao-Scott Chi-square test and Fisher's exact test were used to identify factors with prognostic potential that were subjected to bivariate and multivariate analyses with a binary logit regression model to assess associations. Qualitative data were managed using Microsoft Excel and MAXQDA 10. # Results A total of 231 survey responses were collected and seven interviews conducted. MOT was found to be of "somewhat" contextual fit with population estimates of (preference: 29.61%, CI= 23.96-35.27; acceptability: 95.99%, CI= 93.79-98.18), and "strong" feasibility (willingness to use: 95.56%, CI= 93.78-97.35; workplace ICT availability: 82.09%, CI= 77.50-86.68). Work area was found as a major predictor of MOT contextual fit and feasibility, where the probabilities of MOT preference, acceptability, willingness to use, and workplace ICT availability were 42% lower (CI= 0.58-0.59), 99% lower (CI= 0.01-0.14), 95% lower (CI= 0.01-0.40), and 2.57 (CI= 1.22-5.40) times higher respectively for public health workers in rural areas compared to those in urban areas. Triangulating the quantitative and qualitative data showed issues around training resources accessibility, training characteristics, and training environment as factors that contributed to the contextual fit and feasibility ratings. # Conclusions This study findings provided evidence for the contextual fit and feasibility of MOT with geographic disparities, including associated factors that could inform prioritization, adaptation, and scale up of e-learning interventions through the equity lens towards improving the public health workforce capacity for global health security.